Philippine statistical system in the wake of the emerging data revolution and digitization - Jose Ramon G. Albert; Jana Flor V. Vizmanos (Philippine Institute for Development Studies (PIDS), 2019)
The Philippine Statistical System (PSS), the government-wide system of providing statistical information and services, consists of the Philippine Statistics Authority (PSA) and other data producers in the public sector across all administrative levels; the Philippine Statistical Research and Training Institute (PSRTI), the research and training arm of the PSS; and the PSA Board (a policy-making body on statistical matters). Data producers release official statistics, i.e. data aggregates, sourced from primary data collections (such as surveys, censuses, administrative reporting systems), and compilations of secondary data. The current PSS structure is a result of Republic Act (RA) 10625, also called the Philippine Statistical Act of 2013, which envisions the PSS to be more responsive to requirements for national development planning. In the wake of the many disruptions from various technologies of the Fourth Industrial Revolution and the concomitant digitization and data revolution, this study looks into how the PSS fares in the production and communication of (official) statistics required for development planning. It also examines how governance and other issues, such as open data and confidentiality, influence various dimensions of data quality (relevance, accuracy, timeliness, accessibility, interpretability, and coherence), as well as trust in data, the data ecosystem and the enabling environment of the PSS. The report points out that RA 10625 defined an inter-agency PSA Board rather than an expert committee as the country's Statistics Policy Council, as was recommended by the Valdepe\~nas Committee. This effectively eliminated a mechanism for external review of the PSA and the PSS. The conversion of Technical Committees into Inter-Agency Committees further weakened outside expert input to PSA and the PSS. Agriculture and industry statistics remain very weak with PSA still relying on faulty procedures carried out by the former Bureau of Agricultural Statistics. Industry statistics weaknesses have been with the former National Statistics Office (NSO) from the beginning on account of defective sampling frames that do not readily track and deaths of firms. [...]
Keywords: 330; Philippine statistical system; official statistics; data revolution; digitization; data quality; trust in data